Mandatory national language requirements in higher education - Kamerlin, Shina Caroline Lynn ; 0000-0002-3190-1173 (EMBO Reports, 2024)
Some countries try to curb internationalisation in academia or require that foreign scientists take language courses. While this is done for the wrong reasons, learning the language of the host country has great benefits for academic staff. [Image: see text]
Keywords: Humans; Language; Universities